Mass spectrometry : - Hoffmann, Edmond de (Wiley, 2007)
The latest edition of a highly successful textbook, Mass Spectrometry, Third Edition provides students with a complete overview of the principles, theories and key applications of modern mass spectrometry. All instrumental aspects of mass spectrometry are clearly and concisely described: sources, analysers and detectors. Tandem mass spectrometry is introduced early on and then developed in more detail in a later chapter. Emphasis is placed throughout the text on optimal utilisation conditions. Various fragmentation patterns are described together with analytical information that derives from the mass spectra.